PENGARUH PGPR (Plant Growth Promoting Rhizobacteria), KAPUR, DAN KOMPOS PADA TANAMAN KEDELAI DI ULTISOL CIBINONG, BOGOR - Aditya Putri Utami; Dwi Agustiyani; Eko Handayanto (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Ultisols are potential for growing soybean However, the soils are considered as acid soils having pH <5,5 hindering availability of several nutrients to support plant growth. The problem can be overcome by application of fertilizers and soil amendment fertilization. This study that was aimed to elucidate the effects of application of PGPR (Plant Growth Promoting Rhizobacteria), lime, and compost on soybean growth on an ultisol of Bogor, used RALF (Factorial Complete Random Design) with 2 factors. The first factor was planting medium with 2 levels (Soil + Compost) and (Soil + Lime) and second factor of PGPR formula with 5 levels (F0 control, F1 soybean bacteria formula, F2 bacterial formula of Root and Tuber Crops Institute, F3 bacterial formula of beans, and F4 formula bacteria of other plant). The results showed that soil + compost treatment had more effect on soil biochemical and plant growth than lime + soil. The treatment of soybean bacteria formula (F1) was most effective in increasing ammonium, nitrate and total population of bacteria. The treatment of bacterial formula of Root and Tuber Crops Institute (F2) had an effect of soil plant growth.